An in situ copper plated boron-doped diamond microelectrode array for the sensitive electrochemical detection of nitrate - Ward-Jones, S; Banks, C; Simm, A; Jiang, L; Compton, R (2005)
The first example of using a copper microelectrode array for use in electroanalysis is explored and exemplified with the electroanalytical quantification of nitrate. The analytical approach is based upon the in situ deposition of copper at a boron-doped diamond (BDD) microelectrode array. The immobilized copper layer is electrocatalytic for nitrate reduction and exhibits an analytically useful range from 1.2 to 124 μM with a marked selectivity for nitrate ion over nitrate, with a limit of detection of 0.76 μM. The analytical applicability was examined through standard addition determinations of nitrate in drinking and river water samples. © 2005 Wiley-VCH Verlag GmbH and Co. KGaA.